2021
DOI: 10.1016/j.bj.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of GPR56/ADGRG1 in health and disease

Abstract: GPR56/ADGRG1 is a versatile adhesion G protein-coupled receptor important in the physiological functions of the central and peripheral nervous systems, reproductive system, muscle hypertrophy, immune regulation, and hematopoietic stem cell generation. By contrast, aberrant expression or deregulated functions of GPR56 have been implicated in diverse pathological processes, including bilateral frontoparietal polymicrogyria, depression, and tumorigenesis. In this review article, we summarize and discuss the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 104 publications
0
40
0
Order By: Relevance
“…GPR56 transcripts were broadly detected in the brain, thyroid, pancreas, kidney, testis, skeletal muscle, and the hematopoietic system [88]. Consistently, GPR56 has been found to be functionally important in diverse physiological and pathological processes [88].…”
Section: Adgrg1/gpr56mentioning
confidence: 83%
See 2 more Smart Citations
“…GPR56 transcripts were broadly detected in the brain, thyroid, pancreas, kidney, testis, skeletal muscle, and the hematopoietic system [88]. Consistently, GPR56 has been found to be functionally important in diverse physiological and pathological processes [88].…”
Section: Adgrg1/gpr56mentioning
confidence: 83%
“…GPR56 transcripts were broadly detected in the brain, thyroid, pancreas, kidney, testis, skeletal muscle, and the hematopoietic system [88]. Consistently, GPR56 has been found to be functionally important in diverse physiological and pathological processes [88]. The most recognized biological function of GPR56 is its essential role in the normal cerebral cortical development as its loss-off-function resulted in bilateral frontoparietal polymicrogyria (BFPP), a rare genetic disorder affecting the cerebral cortex, in the frontal and parietal lobes of the brain [17].…”
Section: Adgrg1/gpr56mentioning
confidence: 99%
See 1 more Smart Citation
“…GPR56 was expressed in mouse Sertoli cells as well as Mullerian duct epithelium of avian female gonads [ 67 , 68 ]. For the general review of the role of GPR56 in health and disease, the readers are referred to a recent review article [ 69 ].…”
Section: Overview Of the Adgrg1/gpr56 Receptormentioning
confidence: 99%
“…As such, the receptor is also involved in abnormal functioning of the nervous system as well as cancer development. GPR56 is consequently an important target for developing diagnostic tools and therapeutics [ 17 ]. A recent study for example showed that chronic, stress-induced downregulation of GPR56 leads to depression with suicidal tendencies and poor or no response to treatment with antidepressants.…”
Section: Also In This Issuementioning
confidence: 99%